Narciclasine attenuates LPS-induced acute lung injury in neonatal rats through suppressing inflammation and oxidative stress - Duan, Qingning; Jia, Yin; Qin, Yan; Jin, Yingji; Hu, Haozhong; Chen, Jiebin (Bioengineered, 2020)
Acute lung injury (ALI) is a life-threatening disorder related to serious pulmonary inflammation. Narciclasine exhibits strong anti-inflammation activity and attenuates the reactive oxygen species (ROS) production. The present study aims to investigate the underlying mechanism related to the effect of narciclasine on the pathogenesis of neonatal acute lung injury (ALI). Narciclasine attenuated LPS-induced pathological injury and pulmonary edema. In addition, narciclasine suppressed the secretion of inflammatory cytokines, including necrosis factor-α (TNF-α), Interleukin (IL-6), IL-1β, monocyte chemotactic protein-1 (MCP-1) in serum, and inhibited the expressions of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) in lung tissues of neonatal ALI rats. Furthermore, narciclasine alleviated oxidative stress and apoptosis in lung tissues. Importantly, narciclasine exerted an inhibition effect on NF-κB nuclear translocation and activation of Toll-like Receptor 4 (TLR4)/Nuclear factor (NF)-κB/Cyclooxygenase 2 (Cox2) signaling pathway. Taken together, narciclasine protected against lung injury via inhibition effect on excessive inflammation, oxidative stress and apoptosis, hence, narciclasine may be considered as an effective and novel agent for clinical therapeutic strategy of ALI Treatment.